Light output improvement of GaN-based light-emitting diodes grown on Si (111) by a via-thin-film structure *Project supported by the National Key R&D Program (Nos. 2016YFB0400100, 2016YFB0400104), the National Natural Science Foundation of China (Nos. 61534007, 61404156, 61522407, 61604168, 61775230), the Key Frontier Scientific Research Program of the Chinese Academy of Sciences (No. QYZDB-SSW-JSC014), the Science and Technology Service Network Initiative of the Chinese Academy of Sciences, the Key R&D Program of Jiangsu Province (No. BE2017079), the Natural Science Foundation of Jiangsu Province (No. BK20160401), and the China Postdoctoral Science Foundation (No. 2016M591944). This work was also supported by the Open Fund of the State Key Laboratory of Luminescence and Applications (No. SKLA-2016-01), the Open Fund of the State Key Laboratory on Integrated Optoelectronics (Nos. IOSKL2016KF04, IOSKL2016KF07), and the Seed Fund from SINANO, CAS (No. Y5AAQ51001). (April 2018) - Li, Zengcheng; Feng, Bo; Deng, Biao; Liu, Legong; Huang, Yingnan; Feng, Meixin; Zhou, Yu; Zhao, Hanmin; Sun, Qian; Wang, Huaibing; Yang, Xiaoli; Yang, Hui
Abstract: This work reports the fabrication of via-thin-film light-emitting diode (via-TF-LED) to improve the light output power (LOP) of blue/white GaN-based LEDs grown on Si (111) substrates. The as-fabricated via-TF-LEDs were featured with a roughened n-GaN surface and the p-GaN surface bonded to a wafer carrier with a silver-based reflective electrode, together with an array of embedded n-type via pillar metal contact from the p-GaN surface etched through the multiple-quantum-wells (MQWs) into the n-GaN layer. When operated at 350 mA, the via-TF-LED gave an enhanced blue LOP by 7.8% and over 3.5 times as compared to the vertical thin-film LED (TF-LED) and the conventional lateral structure LED (LS-LED). After covering with yellow phosphor that converts some blue photons into yellow light, the via-TF-LED emitted an enhanced white luminous flux by 13.5% and over 5 times, as compared with the white TF-LED and the white LS-LED, respectively. The significant LOP improvement of the via-TF-LED was attributed to the elimination of light absorption by the Si (111) epitaxial substrate and the finger-like n-electrodes on the roughened emitting surface.